Evolusi Sistem Bahan Bakar LPG: Tinjauan Literatur - Muji Setiyo; Budi Waluyo (Rekayasa Mesin, 2019)
This article presents an analysis of the development of fuel system technology in Liquified Petroleum Gas (LPG) vehicles compared to the development of a fuel system in a gasoline engine. We found that over the past 100 years of using LPG as an alternative fuel, there have been changes in LPG kits for six generations. The first and second-generation LPG kits are similar to the concept of a carburetor, LPG and air mix in front of the throttle valve through a mixer. The third-generation of LPG kits is equivalent to K-Jetronik on a gasoline engine. The fourth and fifth-generation follow the development of a multi-point multi-point injection system and the sixth generation follows the workings of gasoline direct injection (GDI). The sixth-generation of LPG kits, where LPG is injected into the combustion chamber, has an advantage in volumetric efficiency but due to high combustion chamber temperatures, it is necessary to develop injectors that are resistant to high temperatures.